End of life in patients under the care of paediatric palliative care teams. Multicentre observational study - Maria José Peláez Cantero; Jose Miguel Morales Asencio; Lucia Navarro Marchena; Maria del Rosario Velázquez González; Jesús Sánchez Echàniz; Laura Rubio Ortega; Ricardo Martino Alba (Elsevier, 2022)
Introduction: Around 2000 children and adolescents die each year in Spain, however, we know little about the particularities of deaths in paediatrics. The purpose of this study is to document the characteristics of patients who die in the care of paediatric palliative care teams in Spain. Patients and Methods: Retrospective, descriptive, multicentre study. Fourteen teams from all over the country participated. Results: Data were obtained from 164 patients. In most cases the underlying disease stemmed from oncological, neurological or neuromuscular processes. The median age at death was 6.9 years (RIC 11.2). The median follow-up time by the team was 0.3 years (RIC 0.8 years). The most frequent symptoms in the last week of life were dyspnoea, pain, increased secretions and sleep disorders. The median number of drugs administered to each patient one week prior to death was 6 (RIC 4). The place of death for 95 of the patients (57.9%) was hospital while 67 (40.9%) died at home. Conclusions: There was a wide age range of patients and they had substantial exposure to polypharmacy. The follow-up time shows that patients have late access to palliative care programmes. An effort should be made to introduce this care earlier rather than relegating it to the end of life. In Spain there is an unequal distribution of resources and not all teams can provide care at home. The place of death should be interpreted with caution. Resume: Introducción: Cada año fallecen en España alrededor de 2000 niños y adolescentes; sin embargo, conocemos poco las particularidades que envuelven a la muerte en pediatría. El objetivo de este estudio es documentar las características de los pacientes que fallecen a cargo de los Equipos de Cuidados Paliativos pediátricos en España. Pacientes y Métodos: Estudio retrospectivo, descriptivo y multicéntrico. Participaron 14 equipos de todo el territorio nacional. Resultados: Se obtuvieron datos de 164 pacientes. En la mayoría la enfermedad de base eran procesos oncológicos, neurológicos y neuromusculares. La mediana de edad al fallecimiento fue de 6.9 años (RIC 11.2). La mediana de tiempo de seguimiento por el equipo fue de 0.3 años (RIC 0.8 años). Los síntomas más frecuentes en la última semana de vida fueron disnea, dolor, aumento de secreciones y trastornos del sueño. El número de fármacos que se administraban a cada paciente una semana previa al fallecimiento tuvo una mediana de 6 (RIC 4). El lugar de fallecimiento de 95 de los pacientes (57.9%) fue el hospital y de 67 (40.9%) fue su domicilio. Conclusiones: Los pacientes presentaban un amplio rango de edad y una exposición sustancial a la polifarmacia. El tiempo de seguimiento nos muestra el acceso tardío a los programas de Cuidados Paliativos, deberíamos hacer un esfuerzo para la introducción temprana de estos cuidados y que no quede relegada al final de vida. En España existe una distribución desigual de recursos, sin que todos los equipos tengan la posibilidad de atención domiciliaria, por lo que el lugar de fallecimiento debemos interpretarlo con cautela.